THE RELATIONSHIP BETWEEN THE INDIVIDUAL AND THE STATE IN THE CONTEXT OF THE THEORY OF JUSTICE - Оксана МЕЛІКОВА (Епістемологічні дослідження у філософії, соціальних і політичних науках)
The article is devoted to the study of an important problem - how to build a reliable model of interaction between the state and the individual based on the idea of social justice in modern society. This issue is especially relevant against the background of rapid political and social changes that require the unification of citizens around common values and a vision of the future. Renewal of the ideological foundation, which is the basis of national identity, as well as the formation of a unified outlook on social justice can become a powerful driver of the state’s development. The main goal of the article is to find effective approaches to the modernization of society through the creation of a nationwide concept of social justice, which is able to unite society around common values and contribute to the formation of trust in social institutions. For this, the article refers to the theory of John Rawls «justice as honesty», which has already proven itself in European countries as an effective basis for establishing social harmony. The study also examines two main ethical concepts – «correctness» and «goodness», which complement Rawls’s theory and provide an opportunity to build a more stable ideological foundation for Ukraine. The research methodology includes systemic-analytical, historical, comparative and structural-functional approaches, which allow a comprehensive assessment of how mass attitudes and social attitudes affect the formation of the concept of justice in the country. Sociological methods were also used, which helped to identify shortcomings in the attitude of citizens towards state institutions and to determine the main directions for strengthening public consensus. The results of the study demonstrate that there is a lack of a generally accepted vision of social justice in Ukrainian society, and the lack of a single ideological reference point makes it difficult for citizens to consolidate around national priorities. Sociological surveys indicate a low level of trust in state institutions, which significantly slows down reform processes. Therefore, the implementation of the concept of social justice requires active cooperation between the public and the political elite, efforts to restore trust and build a positive vision of the future. As a result, the author of the article concludes that in order to build a just and prosperous society, it is necessary to update the existing approaches to social policy. Only through the creation of a common ideological field based on justice and an active citizen position, it is possible to achieve sustainable development of the country and ensure the consolidation of the nation.